Promising Response of Olaparib in Patient With Germline -Mutated Metastatic Gastric Cancer - Kok Hoe Chan MD; Darius Rutazanaa MD; Curtis Wray MD; Nirav Thosani MD; Victor Yang MD; Putao Cen MD (Journal of Investigative Medicine High Impact Case Reports, 2024)
Gastric cancer ranks as the fifth leading cause of global cancer incidences, exhibiting varied prevalence influenced by geographical, ethnic, and lifestyle factors, as well as Helicobacter pylori infection. The ATM gene on chromosome 11q22 is vital for genomic stability as an initiator of the DNA damage response, and mutations in this gene have been associated with various cancers. Poly ADP-ribose polymerase (PARP) inhibitors, such as olaparib, have shown efficacy in cancers with homologous recombination repair deficiencies, notably in those with ATM mutations. Here, we present a case of a 66-year-old patient with germline ATM-mutated metastatic gastric cancer with very high CA 19-9 (48 000 units/mL) who demonstrated an exceptional response to the addition of olaparib to chemo-immunotherapy and subsequent olaparib maintenance monotherapy for 12 months. CA 19-9 was maintained at low level for 18 months. Despite the failure of a phase II clinical trial on olaparib in gastric cancer (NCT01063517) to meet its primary endpoint, intriguing findings emerged in the subset of ATM-mutated patients, who exhibited notable improvements in overall survival. Our case underscores the potential clinical utility of olaparib in germline ATM-mutated gastric cancer and emphasizes the need for further exploration through larger clinical trials. Ongoing research and clinical trials are essential for optimizing the use of PARP inhibitors, identifying biomarkers, and advancing personalized treatment strategies for gastric cancer.